2019
DOI: 10.1108/intr-08-2018-0389
|View full text |Cite
|
Sign up to set email alerts
|

Engaging with TV events on Twitter

Abstract: Purpose The purpose of this paper is to explore the interrelationship between television (TV) consumption (viewing ratings), engagement behaviors of different actors on Twitter (TV programs, media, celebrities and viewers) and the content of engagement behaviors (affective, program-related and social content). Design/methodology/approach TV ratings and Twitter data were obtained. The content of tweets was analyzed by means of a sentiment analysis. A vector auto regression model was used to understand the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…(2015), video posts on Twitter were negatively correlated with TV show ratings. Similarly, Segijn et al. (2019) also found a negative relationship between Twitter posts and TV rating.…”
Section: Literature Reviewmentioning
confidence: 83%
See 2 more Smart Citations
“…(2015), video posts on Twitter were negatively correlated with TV show ratings. Similarly, Segijn et al. (2019) also found a negative relationship between Twitter posts and TV rating.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Conversely, according to Min et al (2015), video posts on Twitter were negatively correlated with TV show ratings. Similarly, Segijn et al (2019) also found a negative relationship between Twitter posts and TV rating. In addition, research on social TV messages has mostly focused on the use of Twitter (e.g.…”
Section: Relevant Studies On Social Tvmentioning
confidence: 83%
See 1 more Smart Citation
“…However, our study is at the macro-level, which attempted to determine the relationship between social media and mass media in comprehensive trend movements. Segijn et al conducted an empirical study on the relationship between TV consumption and Twitter content [12]. They developed a vector auto regression (VAR) model for Twitter posts and TV viewing and collected data on live music event broadcasts to confirm the validity of the model.…”
Section: Copyright Cmentioning
confidence: 99%
“…Among the methods of studying online consumer behaviour, the predominant ones measured are through so-called online engagement metrics, including the number of users, click-through rates, page views, content likes and comments, depending on the platform (Muñoz-Expósito et al, 2017). It is also possible to take as a basis the motivation of the individual resulting from their experience with the object, manifested in object behaviour, and viewer engagement understood as the attitude towards the brand in terms of likes, comments and shares (Segijn et al, 2019). This approach will be the basis for this article.…”
Section: Use Social Media For Marketingmentioning
confidence: 99%